Strategi Membangun Hubungan dengan Pelanggan dalam Mendukung Keberlangsungan Usaha pada Toko Rentengan Berlian Raya PPS - Faiz Awaludin Firmansya Budiyantoro; Hadi Ismanto (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze customer relationship strategies in supporting business sustainability at Toko Rentengan Berlian Raya PPS. The research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews with the business owner, employees, and customers, as well as documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that customer relationship strategies are implemented through friendly service, effective communication, the availability of products that meet customer needs, convenient transaction processes, and efforts to maintain long-term relationships with customers. These strategies contribute to increased customer satisfaction and loyalty, as reflected in repeat purchases, greater customer trust, and positive word-of-mouth recommendations. The study also reveals that although Toko Rentengan Berlian Raya PPS has not yet implemented a system-based Customer Relationship Management (CRM), the fundamental principles of CRM have been applied in its daily business operations. These practices have positively contributed to business sustainability by maintaining sales stability and improving the store's competitiveness in the retail market. The study implies that business owners should continuously improve service quality, strengthen communication with customers, and utilize digital media as an effective tool for building customer relationships to ensure long-term business sustainability.